THE EMERGENCE OF STATES IN WORLD HISTORY - Ikromova Marhabo Muzaffar kizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract   This article analyzes in detail the historical development of the concept of the state, the process of its emergence and the main factors that influenced its formation. It  is  shown  that  the  development  of  agriculture,  social  stratification,  political centralization,  religious  and  military  factors  are  of  great  importance  in  the  early formation  of  states.  The  process  of  the  emergence  of  states  is  studied  using  the examples of ancient Mesopotamian, Egyptian, Chinese and Indian civilizations. The article  also  covers  the  role  of  the  concept  of  the  state  in  society,  its  stages  of development and its impact on the modern era.